Association between native mother tongue with the educational level reached in the Peruvian population, 2022 - Guevara-Tirado, Alberto (2023)
The objective was to determine if the type of mother tongue practiced in the Peruvian population is associated with educational level, literacy level, age, sex, and geographic domain. A descriptive, retrospective, cross-sectional study from the national household survey-2022 was carried out. The sampling was probabilistic, of areas, stratified. The Chi-square test was performed. The variables were: mother tongue, age, educational level, geographic domain, sex, and literacy. 4.2% and 0.5% of native language speakers reached university and postgraduate level, respectively, in contrast to Spanish speakers with 12.4% and 1.3% respectively. 65.2% of native language practitioners belong to the Sierra, 48.7% of native language speakers do not know how to read or write, adolescents are the age group that speaks the most Spanish while intermediate and older adults speak mainly native languages. A statistically significant association was found in all groups (p=0.000) except for sex (p=0.126). In conclusion, the type of mother tongue is associated with the educational level attained and other sociodemographic barriers in the Peruvian population. It is necessary to reduce the gaps in inequality of educational opportunities in the affected population in a more committed way.